2023
DOI: 10.1108/jmhtep-05-2022-0038
|View full text |Cite
|
Sign up to set email alerts
|

The practice of incident reporting and management: current challenges and opportunities for mental health trusts in England

Abstract: Purpose New patient safety frameworks are being implemented to improve the impact of incident reporting and management across the National Health Service (NHS) in England. This study aims to examine the current practices in this domain of patient safety in a sample of mental health trusts, a setting in which limitations in the current practice of serious incident management have been reported. The authors present key recommendations to maximise the opportunities to improve current incident reporting and manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The study sample is the same as our study examining patient safety systems (Wood et al , 2023a), but necessary detail concerning the methods is provided here so that this paper can be read on its own and to provide sufficient detail to enable replicability (Leung, 2015). This qualitative interview study aims to build on the findings of our questionnaire study regarding the practice of incident reporting and management (Wood et al , 2023b). Semi-structured interviews were selected as an appropriate method to understand professionals’ perspectives about supporting a patient safety culture in local systems, with a particular focus on improving the effectiveness of serious incident management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study sample is the same as our study examining patient safety systems (Wood et al , 2023a), but necessary detail concerning the methods is provided here so that this paper can be read on its own and to provide sufficient detail to enable replicability (Leung, 2015). This qualitative interview study aims to build on the findings of our questionnaire study regarding the practice of incident reporting and management (Wood et al , 2023b). Semi-structured interviews were selected as an appropriate method to understand professionals’ perspectives about supporting a patient safety culture in local systems, with a particular focus on improving the effectiveness of serious incident management.…”
Section: Methodsmentioning
confidence: 99%
“…The selected sampling approach was purposive, as this approach provides access to particular perspectives on research areas of interest (Smith et al , 2022). DW reviewed responses from the precursor questionnaire study (Wood et al , 2023b) and selected trust where it was felt that follow-up would provide substantial new insights (Malterud et al , 2016). For example, in the questionnaire study, one participant reported that their trust used a cohort of external investigators to review serious incidents.…”
Section: Methodsmentioning
confidence: 99%